Health Behaviors of Cancer Survivors and Population Controls From the National Health Interview Survey (2005-2015) - Boyd, Patrick (JNCI Cancer Spectr, 2020)
BACKGROUND: Population-based data from the National Health Interview Survey were examined to provide estimates of a wide range of health behaviors in cancer survivors (ie, physical activity, sun protection, alcohol use, cigarette and e-cigarette use, sleep, and diet) and trends over time. METHODS: Data were collected from 92 257 participants across 3 waves of the National Health Interview Survey. A total of 8050 participants reported having had cancer (2428 in 2005, 2333 in 2010, 3289 in 2015). Weighted and adjusted odds ratios (OR) between cancer survivors and controls were calculated using logistic and multivariable regressions in SPSS, and trend analyses from 2005 to 2015 were conducted. All statistical tests are 2-sided. RESULTS: After adjusting for demographics (2005-2015), cancer survivors, compared with controls, were more likely to wear sunscreen (OR = 1.41, 95% confidence interval [CI] = 1.32 to 1.51) and protect their skin (P < .001) and were less likely to tan indoors (OR = 0.81, 95% CI = 0.69 to 0.95), but reported less sleep (OR = 0.91, 95% CI = 0.85 to 0.98). In adjusted models, no differences were found for physical activity, sunburns, alcohol use, smoking, e-cigarette use, and diet. Smoking rates for cancer survivors decreased from 2005 to 2015 (P < .001) and physical activity increased (P = .02), but physical activity was not statistically significant after adjusting for multiple comparisons. All other health behavior rates for cancer survivors were unchanged from 2005 to 2015 (P > .14). CONCLUSION: After adjusting for covariates, cancer survivors exhibited healthier sun protection, but not sleep behaviors, compared with controls. Cancer survivors (and controls) exhibited decreased smoking rates over time. These results may inform interventions focused on improving cancer control and prevention of other chronic conditions among cancer survivors.